OPTIMALISIERUNG UND MODIFIZIERUNG VON VERZAHNTEN GETRIEBEPAAREN - Bercsey, Tibor; Árvai, Zoltán; Hegyháti, József (Periodica Polytechnica Mechanical Engineering, 1985)
Digital simulation of the engagement of cogged transmission-pairs facilitates the optimization of the geometric parameters of transmission elements and the determination of modification ensuring favourable circumstances for load-exchange. Numeric analysis of spyroid and toroid transmissions demonstrate the applicability-limit of purpose-functions and optimization criteria carried out from the point of view of hydrodynamic loading. Method, worked out for the modification of Wildhaber-Novikov eogs ealls our attention to the analysis of heavy-Ioad and capacity cogged transmission-pairs, taking into consideration their flexible transformation as well.